PENERAPAN AZAS PENGELOLAAN KEUANGAN DESA - Dewi Kirowati; Qimyatussa'adah Qimyatussa'adah; Sugiharto Sugiharto (Pusat P2M Politeknik Negeri Batam, 2017)
Village as a direct government in contact with the community becomes the main focus in government development, this is because most of Indonesia is in rural area. Something special President Bambang Susilo Yudhoyono ratified the new Law No. 6 of 2014 on Villages signed on 15 January 2015. This law explains that villages receive funding of 10% of the state budget, where the funds will not pass through intermediaries. Thefunds will go straight to the village. But the nominal amount is different depending on the village's geography, population, and death rate. Increased village revenue is certainly required to have accountability reports in a transparent and accountable manner. Village finance gleaned from Permendagri No. 113 Year 2014 are all the rights and obligations of the Village which can be assessed with money and everything in the form of money and goods related to the implementation of the rights and obligations of the Village. This research is a researcher wants to describe the implementation of village financial management principle and know accountability of accountability report of village fund in Temboro Village, Karas District, Magetan RegencyKeywords: Village Finance, Village Financial Management, Accountability